Roads, Railroads, and Decentralization of Chinese Cities - Baum-Snow, Nathaniel; Brandt, Loren; Henderson, J. Vernon; Turner, Matthew A.; Zhang, Qinghua (The Review of Economics and Statistics, 2017)
We investigate how urban railroad and highway configurations have influenced urban form in Chinese cities since 1990. Each radial highway displaces 4% of central city population to surrounding regions, and ring roads displace about an additional 20%, with stronger effects in the richer coastal and central regions. Each radial railroad reduces central city industrial GDP by about 20%, with ring roads displacing an additional 50%. We provide evidence that radial highways decentralize service sector activity, radial railroads decentralize industrial activity, and ring roads decentralize both. Historical transportation infrastructure provides identifying variation in more recent measures of infrastructure.